Developing a Method to Measure Public Prosperity Gap between Ideal and Current Conditions of a Local Government: A Public Financial Management Perspective - Prabowo, Raden Adiguna; Ritonga, Irwan Taufiq (The Indonesian Journal of Accounting Research, 2025)
This study aims to develop a method for measuring the public prosperity gap between the ideal condition, as stated in the constitution, and the current condition of a local government, utilizing the Purchasing Power Parity (PPP) Theory and the concept of service-level solvency. This study uses the City of Melbourne as a representation of ideal conditions and the City of Jakarta as a representation of current conditions. The model developed in this study can accurately measure the prosperity gap that occurs and assess its severity. The limitation of this study is the use of the service solvency in general terms to measure the prosperity of the community. The use of specific solvency should improve the accuracy of the prosperity gap analysis. However, these limitations do not reduce the validity of the model.